Survey of environmental health conditions in relation to safety in public primary schools in Egbeda Local Government area of Oyo State Nigeria (2013)
The importance of the school environment to the primary school teacher should not be underestimated as the best of health teaching is done by example. Teachers register complaints about noisy environment, lack of water, poor playground and insufficient toilet facilities among other problems. The need to be constantly alert to observe school buildings, fencing, play ground and other possible hazardous condition that may affect the safety of pupils has become very important, not only to the school but also to the community. Seven research questions were drawn. Purposive sampling was adapted to survey 74 public primary schools. Data collected were analyzed using percentages. The study revealed that the conditions of more than 60% of public primary schools in Egbeda Local Government Area of Oyo State may affect safety of the school community members. The study also shows that most of the schools did not have adequate water supply, sanitation and waste disposal facilities. In recommendation, the ministries of education, health and environment should ensure regular routine inspection of public primary schools with the aim of creating a friendly, safe and sustainable healthful school environment that will improve the process of teaching and learning that will result in favourable learning outcomes.